Organic Photovoltaic Cells Based on PbPc Nanocolumns Prepared by Glancing Angle Deposition - Yang Liu; Fujun Zhang; Jian Wang (International Journal of Photoenergy)
Organic small material lead phthalocyanine (PbPc) nanocolumns were prepared via glancing angle deposition (GLAD) on indium tin oxide (ITO) coated glass substrates. Organic electron acceptor materials fullerene (C60) was evaporated onto the nanocolumn PbPc thin films to prepare heterojunction structure ITO/PbPc/C60/Bphen/Al organic photovoltaic cells (OPVs). It is worthwhile to mention that C60 molecules firstly fill the voids between PbPc nanocolumns and then form impact C60 layer. The interpenetrating electron donor/acceptor structure effectively enhances interface between electron donor and electron acceptor, which is beneficial to exciton dissociation. The short circuit current density (Jsc) of organic photovoltaic devices (OPVs) based on PbPc nanocolumn was increased from 1.19 mA/cm2 to 1.74 mA/cm2, which should be attributed to the increase of interface between donor and acceptor. The effect of illumination intensity on the performance of OPVs was investigated by controlling the distance between light source and sample, and the Jsc of two kind of OPVs was increased along with the increase of illumination intensity.